Analysis of Work Discipline in Increasing Employee Productivity at PT Metal Fastindo Abadi Tangerang - Andriyani, Vinna (Indonesian Development of Economics and Administration Journal, 2024)
This research is a qualitative research that aims to find out whether the work discipline applied by employees can increase the work productivity of PT Metal Fastindo Abadi Tangerang. This study took 6 (six) respondents, consisting of 4 men and 2 women. The data collection method uses observation, interview and documentation techniques directly to employees. The results of this study indicate that work discipline plays an important role in the performance of employees of PT Metal Fastindo Abadi Tangerang. As a performance assessment, all employees are expected to be disciplined starting from themselves first by attending on time and obeying and obeying the rules in the company so that employees can carry out their responsibilities properly. In addition, to increase the work productivity of PT Metal Fastindo Abadi Tangerang employees, employees are given bonuses in the form of attendance premiums and also rewards from the company if employees work well and exceed the set targets. This has a very good effect on increasing employee work productivity.